Spurring innovation through global knowledge management at Procter & Gamble - Bjo?rkman, Ingmar, (SAGE knowledge. Cases., 2016)
Procter & Gamble is a manufacturing multinational company of consumer goods founded in Cincinnati, US. Since then, the firm has established a worldwide network of research centers and facilities, and developed new innovative products. Here, we examine an example of how knowledge and innovation is a vital aspect of management in multinational companies.